Preaching in the context of ethic violence : a practical theological study within the Calabar synod of the Presbyterian Church of Nigeria - Ekong, Ivan (Stellenbosch : Stellenbosch University, 2011)
Thesis (MTh (Practical Theology and Missiology))--Stellenbosch University, 2011.